VIOLÊNCIAS CONTRA AS MULHERES E A ATUAÇÃO DO PODER LEGISLATIVO PARA O SEU ENFRENTAMENTO: análise das proposições apresentadas nos anos de 2011 a 2018 na Assembleia Legislativa do Maranhão. - ALMEIDA, Mariana Abreu (2019)
The purpose of this dissertation is to analyze the legislative proposals presented by the Maranhão Parliament from 2011 to 2018 on the issue of combating violence against women. Thereunto we sought to understand the problem of violence against women, based on the assumption that patriarchy is one of the pillars of gender inequalities. Indeed it is understood that there is no alternative to gender studies, but overlapping with race and class issues, as they are fundamental in perpetuating and multiplying the effects caused by social inequalities. In order to apprehend the factual reality about the types of violence against women, data and indicators were presented from Brazil and especially from the State of Maranhão, when the urgency of this problem has been proven, which, in its maximum expression – feminicide – makes Brazil the fifth country in the world were more women are killed because of their gender. The reality of Maranhão does not seem more promising, since between 1996 to 2016, the murder of women has increased to a level above 400%. A bibliographical research was carried out in order to recover the history of the conquest of the positive rights of women in Brazil, emphasizing the role of feminist movements that appear as protagonists of these struggles. Being the Legislative Branch the focus of this research, understanding its functions, as well as its dynamics of functioning within the scope of the tripartite powers, especially, its relations with the Executive, proved of fundamental character. After a brief historical contextualization of Maranhão and the Legislative Assembly, the results obtained by the documentary research done through the Legislative Process Support System (SAPL) were presented, which collected, among all the legislative proposals submitted by the legislators within the chosen time frame, those concerning the confrontation of violence against women in the State of Maranhão.